(untitled) (Islamic Sciences Journal, 2024)
ABSTRACT You cannot interpret any literary text without being aware of the circumstances of its writing and mastering the language in which it was written. This applies to any ordinary text, so how about if it is a sacred text that God revealed to the heart of His Prophet? The task of interpreting the sacred text will be more difficult and heavier, but in the era of YouTube, the nation has suffered. There are people who interpret the Qur’an with no knowledge of the Arabic language as a grammar or explanation, nor of scientific research as a method and principles, nor of the Prophet’s Sunnah as a chain of transmission and text. Their concern is fame and appearance in Internet programmes. There were cries for new interpreters of the Qur’an that came after 2013 AD, that is, with the Arab Autumn, which makes us say that there are threads. These people moved for religious and political purposes, and at the forefront of these purposes is to question the origins of Islam, on which the Islamic religion is based. Among these people is those who have afflicted the nation (Ali Mansour Al-Kayyali), who, as he defined himself, is an architect and physicist, not an interpreter. This study aims to show that The books of ancient interpreters are not sacred, but interpretation requires several conditions, the most important of which is that the interpreter must know the Arabic language, its rules, and its etiquette, including grammar, morphology, derivation, and rhetoric. For the purpose of achieving the objectives of the study, its approach is based on critical analysis as a basic approach in order to reach the results that ( Mansour)’s goal was to destabilize the status of the Islamic heritage in the hearts of Muslims in order to present a new understanding of the Qur’an. The study concluded that Al-Kayyali does not have knowledge of the interpreter’s instrument and the Arabic language, and the best evidence is the way he reads the Qur’an, which contains several errors.